GROUNDWATER CONTAMINATION AND DECONTAMINATION IN CHORNOBIL ALIENATION ZONE - SHEVCHENKO, O.; KIRIEIEV, S.; HUDZENKO, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
Rate of self-purification depends on aquifer’s vulnerability, contamination of the source recharging an aquifer or on contamination of rocks on the filtration pathway. Sustainable, smooth changes of 90Sr concentration in the groundwater may support the idea about the absence of additional sources of pollution, steady flow of groundwater and an equilibrium of sorption-desorption processes.